Correction: Facile synthesis of near-infrared bodipy by donor engineering for in vivo tumor targeted dual-modal imaging. Issue 3 (6th January 2022) - An, Feifei; Xin, Jingqi; Deng, Caiting; Tan, Xiaofang; Aras, Omer; Chen, Nandi; Zhang, Xiaohong; Ting, Richard
Abstract : Correction for 'Facile synthesis of near-infrared bodipy by donor engineering for in vivo tumor targeted dual-modal imaging' by Feifei An et al., J. Mater. Chem. B, 2021, 9, 9308–9315, DOI: ; 10.1039/D1TB01883C .